A funds of knowledge approach to developing engineering students' design problem framing skills. Issue 2 (12th January 2022) - Svihla, Vanessa; Chen, Yan; Kang, Sung "Pil"
Abstract: Background: Engineering programs have increasingly incorporated design challenges into courses. These design challenges vary in the degree to which they present complex, ill‐structured, and relevant problems, and therefore may vary in the degree to which they support students to learn to frame design problems. Purpose/Hypothesis: We characterized how first‐year engineering students with little formal design training approach problem framing. We developed design challenges informed by funds of knowledge. We compared the development of problem framing skills in first‐year students who completed these challenges to students who completed more traditional challenges and to students in capstone design. Design/Method: Students completed a pre/post performance‐based assessment of problem framing skills. We analyzed student responses in terms of design requirements, design practices, and design styles . We used descriptive statistics and correlations to characterize how students initially approached problem framing and repeated‐measures ANOVA to compare groups of students. Results: First‐year students approached framing a design problem in one of four primary ways. Compared to students in the original course, they showed growth in attending to an underlying need, considering contexts of use, and depicting design function. Compared to capstone students, they also showed growth in considering stakeholder roles and planning the next steps. Conclusions: Funds of knowledge can provide a means to evaluate possible design challenges as authentic yet accessible for first‐year students, in turn, providing opportunities to support the development of the design problem framing ability.